Clinical, diagnostic features and treatment of orgasmic dysfunctions in anxiety-depressive spectrum disorders - M. I. Yagubov; I. Yu. Kan; I. R. Ayriyants (Лечащий Врач)
Background. The relevance of this study is associated with the wide prevalence of anxiety and depressive disorders, their variability and diversity of comorbidity, including sexual disorders in the form of orgasmic dysfunctions in women and men. The article presents data on the formation of orgasmic dysfunctions in patients with mental disorders, the mutual influence of mental and sexual pathologies, the similarities and differences of orgasmic disorders in men and women, their clinical and therapeutic aspects.Materials and methods. We examined 122 patients (64 women and 58 men) aged 18 to 45 years who sought sexological help. The main research methods were clinical-psychopathological and clinical-sexological using as additional tools: the Hospital Anxiety and Depression Scale (HADS), the Weitel Scale, which allows to determine hypochondriacal traits, the Asthenic State Scale – SHAS and Visual Analogue Scale to measure the subjective perception of orgasmic intensity – The оrgasmometer – male and female versions. To compare the characteristic clinical and psychopathological features of orgasmic dysfunctions in women and men with anxiety-depressive spectrum disorders, in accordance with the ICD-10 diagnostic criteria, patients were divided into two groups. The first group consists of patients with neurotic, stress-related and somatoform disorders (F4), and the second with affective mood disorders (F3).Results. During the study, it was possible to identify the main factors that are a possible predisposition of orgasmic disorders (weak type of sexual constitution, accentuation of character, disturbances in the formation of libido in the form of a delay in the platonic and erotic phases, episodes of generalized anxiety or persistent (at least 3 months) decreased mood with anhedonia and asthenia). The first study group (F4) included patients suffering from neurasthenia, dissociative and somatization disorders in women, and patients with neurasthenia, hypochondriacal and somatization disorders in men. The second group (F3) was homogeneous in mental pathology and was represented by dysthymia. In the structure of anxiety-depressive spectrum disorders in these patients, the features of the formation and clinical course of orgasmic dysfunctions, diagnosis using additional tools in the form of specialized scales were considered, and general principles of therapy were proposed.Conclusion. The presented clinical and psychopathological features of orgasmic dysfunctions make it possible to identify the connection not only with the phenomenon of orgasm, but also with all components of the copulative cycle with affective and other psychopathological symptoms, which allows us to trace the mechanisms of their formation, improve the diagnosis and determination of the prognosis of these disorders, and choose the tactics of treatment and rehabilitation measures , allowing to increase the effectiveness of therapy for orgasmic disorders.